2015
DOI: 10.1007/s12035-015-9495-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Neonatal Sepsis Causes Long-Term Cognitive Impairment

Abstract: Neonatal sepsis is a major cause of morbidity and mortality in neonatal intensive care units. Treatment with antibiotics reduces mortality and morbidity, but neonatal sepsis remains a serious life-threatening condition. The objective of this study was to evaluate cognitive impairment in adult mice submitted to sepsis in the neonatal period. To this aim, 2-day-old male C57BL/6 mice were submitted to sepsis by injection of 25 μg of LPS. Sixty days after, the learning and memory were evaluated. It was observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In one study, authors reported that LPS produced long-lasting increases in depressive- and anxiety-like behaviors in mice (Anderson et al, 2015). Another study showed that 2-day-old male mice injected with LPS exhibited impaired object recognition memory (Comim et al, 2015). However, the underlying mechanisms of depression and recognition memory deficit after LPS injection are not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, authors reported that LPS produced long-lasting increases in depressive- and anxiety-like behaviors in mice (Anderson et al, 2015). Another study showed that 2-day-old male mice injected with LPS exhibited impaired object recognition memory (Comim et al, 2015). However, the underlying mechanisms of depression and recognition memory deficit after LPS injection are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The pro-caspase-1, in turn, proteolytically cleaves pro-interleukin (IL)-1β and pro-IL-18 into their active forms, thus aggravating the inflammatory reaction (Ozaki et al, 2015). Increasing evidence indicates that inflammation may play a crucial role in the pathophysiology of anxiety, major depression, and recognition memory deficit (Bayramgurler et al, 2013; Krugel et al, 2013; Comim et al, 2015; Li et al, 2016). Furthermore, several studies have suggested that NLRP3 inflammasome contributes to the development of depressive disorder and memory deficit (Zhang et al, 2014; Alcocer-Gomez et al, 2015; Li et al, 2016; Sui et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the PI3K/Akt pathway is firmly involved in cerebral ischemia and intracerebral hemorrhage [ 10 , 11 ]. However, although the evidence suggests that preventing cell apoptosis could improve the survival rate in animal models with sepsis [ 12 ], it is also proposed that a pharmacological treatment of LY294002, a PI3K inhibitor, could reverse the existing protective effect of myocardial injury due to sepsis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Near-infrared spectroscopy is being evaluated in high-risk septic patients as a method to monitor brain tissue oxygenation to predict the development of acute neurologic dysfunction (Wood et al, 2016). Interest is growing in identifying biomarkers for sepsis-induced neurologic injury (Bersani et al, 2015), especially because animal models are revealing long-term brain alterations that affect learning and memory and persist into adulthood (Comim et al, 2015;Gao et al, 2015). Targeting neurotoxic inflammatory pathways (Gao et al, 2015) may emerge as an approach that could be guided by specific small-molecule and physiologic biomarkers.…”
Section: Physiologic Biomarkersmentioning
confidence: 99%